Free versus fee-based for information access - Valdez, Andriette S.; Sison, Josephine C.; Mallari, Florenda D.; Cruz, Ma. Divina P. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2001)
This study aimed to determine the viability of fee-based information services in the UPLB Libraries. Traditional library services being offered free, are more popular and heavily utilized by the users. Specifically the objectives of the study were: 1) to determine the adequacy of available fee-based information services to meet the academic and research need of the users; 2) to know the problems encountered in offering fee-based information services; 3) to determine the marketing strategies employed to promote use of fee-based information services; 4) to know the implications of offering fee-based information services in the UPLB libraries.
The respondents of the study were head librarians of the UPLB libraries with the help of some library staff manning the fee-based services. The descriptive method of research was used with survey questionnaire as the data gathering tool and supplemented by interview. Descriptive statistics such as frequencies, percentages and means were used to analyze the data.
Findings of the study were: 1) available fee-based information services are not adequate to meet the academic and research need of the users; 2) problems encountered in offering fee-based information services were lack of computers and other equipment, lack of library staff and experiences in fee-based information services, lack of training for library staff, lack of library facilities and higher client expectations with fee-based services; 3) promotional tools like word-of-mouth and referrals by reference staff, announcements through newsletters and bulletins, signs and posters, promotional brochures and catalogues, live demonstrations and user education were used by librarians to promote and market fee-based information services; 4) the following are the implications of offering fee-based information services: a.) information technology definitely is needed to improve the quality of library services that librarians provide to users, b.) availability of resources which include financial aspects, human and infrastructure, c.) application of marketing strategies is a must to promote fee-based information services to create awareness among users, d.) aside from printed resources, librarians provide expertise to access and exploit the ever-growing number of electronic resources effectively, thus training is needed, e.) fee-based services provide a vehicle for expanding information services to a growing but less library-oriented users, thereby offering a means for information professional to establish their worth or value to seekers of information (Beecher, 1985), f.) Fee-based information services play a significant role in helping librarians rethink their relationship with users and reconsider the value (or value-added) of their work and the services provided (Beecher, 1985), g.) Fees for library services is an additional burden on the part of the users, however, today's users recognize the need for direct charges to maintain, expand and render special library services especially when services need staff expertise.
Respondents recommended the following to improve the available fee-based services: continuous review and improvement of information services in the light of Information Technology, launch massive information campaign to promote use of fee-based services, offer free hands-on training, evaluate existing services, and schedule training for orientations on the use of the services among others.
Vita.
Special Problem (Master of Library and Information Science)
Keywords: Fee-based library services -- Philippines -- Laguna; Information storage and retrieval systems